2009
DOI: 10.1371/journal.pone.0005810
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of IL-1β and VDR Activation Pathways in Human TLR2/1-Induced Antimicrobial Responses

Abstract: Antimicrobial effector mechanisms are central to the function of the innate immune response in host defense against microbial pathogens. In humans, activation of Toll-like receptor 2/1 (TLR2/1) on monocytes induces a vitamin D dependent antimicrobial activity against intracellular mycobacteria. Here, we report that TLR activation of monocytes triggers induction of the defensin beta 4 gene (DEFB4), requiring convergence of the IL-1β and vitamin D receptor (VDR) pathways. TLR2/1 activation triggered IL-1β activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
266
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(282 citation statements)
references
References 49 publications
11
266
2
3
Order By: Relevance
“…Although, to date, this possibility has not been addressed in purified decidual monocytes/macrophages, studies using unpurified first-trimester decidual cells have shown 25OHD-and 1,25(OH) 2 D-mediated induction of cathelicidin (Evans et al 2006). It is also important to recognise that intracrine activation of vitamin D promotes antibacterial responses beyond simple induction of cathelicidin and other antibacterial proteins such as b-defensins (Liu et al 2009). These include the induction of autophagy (Shin et al 2011) and possible effects on intracellular iron concentrations via the iron export modulator hepcidin (Bacchetta et al 2014).…”
Section: Decidual Macrophagesmentioning
confidence: 99%
“…Although, to date, this possibility has not been addressed in purified decidual monocytes/macrophages, studies using unpurified first-trimester decidual cells have shown 25OHD-and 1,25(OH) 2 D-mediated induction of cathelicidin (Evans et al 2006). It is also important to recognise that intracrine activation of vitamin D promotes antibacterial responses beyond simple induction of cathelicidin and other antibacterial proteins such as b-defensins (Liu et al 2009). These include the induction of autophagy (Shin et al 2011) and possible effects on intracellular iron concentrations via the iron export modulator hepcidin (Bacchetta et al 2014).…”
Section: Decidual Macrophagesmentioning
confidence: 99%
“…We recently identified an antimicrobial pathway that is triggered by VDR and results in the cathelicidin and hBD2-mediated killing of M. tuberculosis (16)(17)(18). To evaluate whether this cascade is affected by the restriction of oxygen supply, we cultured M. tuberculosis-infected MDM at 20 or 1% oxygen overnight and measured the expression of VDR by quantitative LightCycler PCR.…”
Section: Regulation Of Vdr and Antimicrobial Peptides At Low Oxygen Tmentioning
confidence: 99%
“…Врожденный иммунитет активируется неза-медлительно, при первом же контакте с ми-кробным антигеном. Этот процесс может стимулировать витамин D, миелоидные и эпи-телиальные клетки, которые экспрессируют Toll-like-рецепторы (TLR) [32][33][34], cYP27B1 и VDR. У людей существуют десять видов TLR, которые активируются посредством их связи с лигандами антигенов микробного происхож-дения.…”
Section: регулирование иммунной системыunclassified